FACTORS RELATED TO DIARRHEA IN SOLOR VILLAGE CERMEE DISTRICT BONDOWOSO - Handono Fatkhur Rahman; Slamet Widoyo; Heri Siswanto; Biantoro Biantoro (Faculty of Nursing, Universitas Jember, 2016)
Diarrhea is one major cause of morbidity and mortality in developing countries. In 2013, in the District Cermee Bondowoso determined extraordinary events diarrhea. Since the determined extraordinary events diarrhea, has never done research the factors related to the incidence of diarrhea. Objectives of this study to determine the factors related to the incidence of diarrhea, especially environmental sanitation, water supply, personal hygiene, food sanitation, the availability of latrines, and fecal waste behavior. This study was a cross-sectional, with sample of 105 patients diarrhea and technique simple random sampling. Result show that factors related to diarrhea include environmental sanitation (p value = 0.000), water supply (p value = 0.005), personal hygiene (p value = 0.010), food sanitation (p value = 0.020), the availability of latrines (p value = 0.031), and fecal waste behavior (p value = 0.044). Environmental sanitation is a factor which influenced the incidence of diarrhea. Health promotion is needed of the factors related to the incidence of diarrhea to prevent diarrhea.